Empowering family with empowering women in empowering assam: A case study of orunodoi scheme in baksa district - Phukan, Ranjeeta (Linguistics and Culture Review, 2021)
Women status and women empowerment these two words very interconnected to each other. Women empowerment can determine by in terms of socio- economic status which influence by an indicators like income, poverty, education, skill, employment opportunities and better health etc. In India, Assam is one of the better positions for women other than North-East state. Because of government always taking initiative and also implementing different types of schemes especially for women. In this paper presenting about the Orunodoi Scheme and their impact factor with implementation for family, women and Assam which is first introduced in October 2020 and but process starting from December 2020. So, only ten-month study highlights with the five objectives by the name of “Empowering family with empowering women in Empowering Assam”.